Designing universal drives for trenchless repair of pipelines - Yemelin, Vyacheslav (Transport, 2011)
The article presents the results of research on a new class of high carrying capacity drives distinguished by the simplicity of designing, universality and high carrying capacity at trenchless repair of pipelines. The paper also describes the dependences of the traction properties of these drives on the major factors of pipelines, technology and design.First Published Online: 12 Apr 2011